2014
DOI: 10.1590/0004-282x20140146
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of subarachnoid hemorrhage is worse in elderly patients

Abstract: Aging is a major risk factor for poor outcome in patients with ruptured or unruptured intracranial aneurysms (IA) submitted to treatment. It impairs several physiologic patterns related to cerebrovascular hemodynamics and homeostasis. Objective: Evaluate clinical, radiological patterns and prognostic factors of subarachnoid hemorrhage (SAH) patients according to age. Method: Three hundred and eighty nine patients with aneurismal SAH from a Brazilian tertiary institution (Hospital do Servidor Público Estadual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, recent retrospective series of EV and MS reported favorable progression in 25-60% of patients, and a significant reduction of mortality (6,10,11,14,16,21,38,39). The present prospective series showed that, after EV or MS treatment, patients with good initial clinical status (WFNS I-III) not only had relatively low mortality (between 15% and 18%); more importantly, the proportion of dependent patients was identical to that in younger patients.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…However, recent retrospective series of EV and MS reported favorable progression in 25-60% of patients, and a significant reduction of mortality (6,10,11,14,16,21,38,39). The present prospective series showed that, after EV or MS treatment, patients with good initial clinical status (WFNS I-III) not only had relatively low mortality (between 15% and 18%); more importantly, the proportion of dependent patients was identical to that in younger patients.…”
Section: Discussionsupporting
confidence: 43%
“…Population aging in Western countries raises questions about extending treatment indications in elderly patients with aneurysmal subarachnoid hemorrhage (aSAH). According to retrospective studies, natural history and clinical outcome at 3 months after endovascular coiling (EV) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) or microsurgical clipping (MS) (6,7,(11)(12)(13)(14)(15)(16) are favorable only in 50-60% of patients older than 70 years. Of note, this trend is also confirmed in patients in their 8 th or 9 th decade of life (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the findings of our study, Pahl et al also concluded that ageing is a risk factor for poor outcomes in patients with ruptured or unruptured intracranial aneurysms. 24 The model also showed that the intercept was significant too, which implicated that there could be other independent variables than those included in this model which could predispose the occurrence of SH. There are several systems for the classification of SH.…”
Section: Discussionmentioning
confidence: 83%
“…The sociodemographic characteristics of the study sample are similar to other studies already described, since the highest occurrence is in women. 3,11,12 This ictus was present in 65% women, with 53% of them in the age range between 41 and 60 years old. Published series on cerebral aneurysm warn that age is an important data to be considered, as they are rare in children and the incidence increases according to age in both sexes.…”
Section: Discussionmentioning
confidence: 99%